Estimating the Demand for Reserve Assets Across Diverse Groups - Bhattacharya, Rina (IMF Working Papers; Working Paper ;, 2018)
This paper takes a fresh look at the determinants of reserves holding with the aim of highlighting similarities and differences in the motives for holding reserves among emerging markets (EMs), advanced economies (AEs), and low-income countries (LICs). We apply two panel estimation techniques: fixed effects (FE) and common correlated effects pooled mean group (CCEPMG). FE regression results suggest that precautionary savings motives, both current account- and capital account-related, are generally the most important determinants of reserves holding across country groups and that their importance has increased for AEs and LICs since the global financial crisis while receding for EMs. Mercantilist motives matter mostly for EMs. Intertemporal motives have been gaining importance everywhere over time. The CCEPMG results confirm the importance of precautionary motives and suggest that current account motives matter only for EMs and LICs and capital account motives matter for all groups while being more important for EMs in both the shortand long runs. The CCEPMG results also point to the importance of taking into account unobserved common factors that affect coefficient estimates and the dynamic process through which reserves adjust to changes. At about 0.6, the speed of adjustment to the long-run equilibrium implies that more than half of the gap between actual and desired reserve holdings is closed within a year.